Mapping Infrastructure and Human Resource Gaps in the Implementation of Indonesia’s Digital Health Policy: A Literature Review - Mujtahidah; Suci Dwi Yanti (Asian Journal of Environmental Research, 2025)
The implementation of digital health policy in Indonesia has encountered various challenges related to both infrastructure and human resources. This literature review aimed to map gaps in digital health infrastructure and workforce capacity across urban, rural, and remote healthcare settings by systematically analyzing relevant national and international studies. Sources included peer-reviewed articles, scoping reviews, and preprints that examined electronic medical records, telemedicine, and other digital health interventions in various geographic and organizational contexts. The analysis revealed that urban areas generally have more advanced digital infrastructure, including integrated health information systems and electronic record platforms, whereas rural and remote regions face limited internet connectivity, insufficient hardware, and low digital literacy among healthcare personnel. Human resource gaps were also observed, including inadequate technical competencies, uneven distribution of staff, and organizational cultures that are not fully prepared to adopt digital health technologies. These disparities highlight the critical need for context-sensitive strategies, such as hybrid solutions combining cloud-based systems in urban centers with offline-capable platforms in low-connectivity regions, comprehensive training programs for healthcare staff, and supportive policies at both local and national levels. By synthesizing the current evidence on infrastructure and human resource gaps, this review provides a comprehensive overview that can guide policymakers, healthcare managers, and researchers in designing targeted interventions, prioritizing resource allocation, and promoting equitable adoption of digital health solutions across Indonesia.